PENGARUH JENIS KEDELAI DAN JUMLAH AIR TERHADAP SIFAT FISIK, ORGANOLEPTIK DAN KIMIA SUSU KEDELAI - Dwi Eva Nirmagustina; Hertini Rani (Jurnal Teknologi & Industri Hasil Pertanian, 2013)
Soybean milk,  a highly nutritious drink especially in protein content, is made ​​from soybean.  Some of the benefits of soybean milk are relatively low price , suitable to be consumed by people with lactose intolerant and for people with diabetes mellitus, favored by children, and easy to manufacture.  Soybean milk quality is determined by the type of soybeans and the amount of water used to dilute.  The research objective was to determine the influence of the type of soybeans (Edamame var. Ryoko, Import, and Local var. Willis) and the amount of water (8, 10, 12 parts) on physical, sensory, and chemical characteristic of soybean milk.  The study was conducted in a complete randomized block design with three replicatations, and replication used as a group.  The data were analyzed using analysis of variance to determine various error estimators and further tested using Duncan's test find whether there is a difference between treatments.  The result showed that viscosity of soybean milk did not influence by the type of soybean but it is influenced by the amount of water. The interaction between the type of soybeans and the amount of water did not affect the organoleptic properties (color, aroma, and taste) of soybean milk. Keywords: milk, soybean, sensory properties, water dilution.